A new species of Amphisbaena Linnaeus (Squamata, Amphisbaenidae) from the state of Maranhão, northern Brazilian Cerrado - Gomes, Jerriane O.; Maciel, Adriano O. (Zootaxa, 2012)
We describe a new species of Amphisbaena based on a single specimen collected in the northern Brazilian Cerrado,municipality of Loreto, state of Maranhão, Brazil. The new species is characterized by presenting a unique combinationof characters including: absence of precloacal pores, body annuli 306, caudal annuli 21, autotomic site in the eighth postcloacal annulus, dorsal sulci absent, 10 dorsal segments and 14 ventral segments in a midbody annulus.